All 'green' composites comprising flax fibres and humins' resins. (8th February 2019) - Sangregorio, Anna; Guigo, Nathanael; van der Waal, Jan C.; Sbirrazzuoli, Nicolas
Abstract: The use of all "green" composite materials is a great environmental option for several applications such as construction or automotive. A new type of all green composites has been prepared by compression moulding flax fibres with humins as the matrix. Humins are macromolecular heterogeneous furanic co-products from biorefinery operations. For the first time the potential of humins as a whole thermoset-like matrix in combination with natural fibres was studied. The raw industrial humins were cross-linked with and without catalyst. The effect of the process conditions on the final properties of the composites was studied. Good tensile properties were measured by tensile test and Dynamic Mechanical Analysis. Observations of the fracture surface were done by Scanning Electron Microscope, revealing a void-free morphology. The study finally focused on the water absorption behaviour, underlining the more hydrophobic nature of the humins' composites compared to the raw flax mat. The good adhesion between the fibre and the matrix was underlined. Humins interacts with the hydrophilic fibres thus creating a good interphase, leading to improved properties. The study demonstrated the possibility of using a biorefinery co-product as a thermoset matrix for preparing composites materials.